Teknik Komunikasi Persuasif Ahmad Rifa’i Rif’an Dalam Dakwah Kepada Kalangan Milenial - Azlika Purnama Sari, Nur Aida (ALAMTARA: Jurnal Komunikasi dan Penyiaran Islam, 2021)
The millennial generation is one of the priority mad'u groups to be preached. Through proper preaching, a generation that upholds religious values ​​and morality will be formed so that they are ready to work on the rare momentum of the demographic bonus. Ahmad Rifa'I Rif'an is one of the Da'Is who have successfully preached among Millennials. Through a book entitled "When God Is No Longer Needed", Rifa'I successfully stirred the reader's feelings until they were persuaded to carry out his invitations in the book. In addition to having entered its sixth edition in three years, this book has also received praise from many great writers and millennial circles who claim to be most satisfied after reading the book. Persuasive communication techniques are one of the factors of success in preaching to millennials. He tries to change the thoughts, feelings, and attitudes of the readers in a subtle, joint dialectic and without patronizing. Using qualitative research, with primary data sources, namely a book entitled "When God Is No Longer Needed", this paper aims to determine Ahmad Rifa'I Rif'an persuasive communication techniques and the suitability of these techniques with the characteristics of the millennial generation. The results showed that the persuasive communication techniques used by Rifa'I were association, integration, pay-off, fear arousing, structuring, authority, narrative and combination techniques. Which all of these techniques are relevant to millennial characteristics.